2018
DOI: 10.1016/j.cgh.2017.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prevalence of Primary Biliary Cholangitis and Reduced Mortality With Treatment

Abstract: In an analysis of data from patients receiving routine clinical care in Fibrotic Liver Disease Consortium health systems, we found that the prevalence of PBC increased from 2004 through 2014, despite steady incidence. Patient demographic and clinical characteristics, as well as UDCA treatment, affected mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 18 publications
7
75
1
3
Order By: Relevance
“…In South Korea, while the incidence of AIH was stable, the prevalence increased gradually from 2009 to 2013 . Rising prevalence of PBC over time has consistently been reported from the Netherlands, northern Italy and Denmark, Hong Kong, Canada, and the USA, and it is a point of debate whether the incidence of PBC is also increasing. In PSC, two systematic reviews concluded that the prevalence as well as the incidence of PSC seem to be increasing .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Korea, while the incidence of AIH was stable, the prevalence increased gradually from 2009 to 2013 . Rising prevalence of PBC over time has consistently been reported from the Netherlands, northern Italy and Denmark, Hong Kong, Canada, and the USA, and it is a point of debate whether the incidence of PBC is also increasing. In PSC, two systematic reviews concluded that the prevalence as well as the incidence of PSC seem to be increasing .…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Estimation of prevalence of AILDs is critical to assess the burden of these diseases on public health. A number of epidemiological studies have been undertaken for AIH, [9][10][11][12][13][14][15][16][17][18][19] PBC, 13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and PSC [37][38][39][40][41][42][43] worldwide, and have shown that prevalence significantly varies depending on regions and ethnicities. Interestingly, several recent studies have indicated that prevalence of all three AILDs has been increasing over the years.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Multiple studies, including data from a 2012 systematic review and a multicenter PBC consortium within the United States, demonstrate the rising prevalence of the disease. [14][15][16] Hence, ensuring timely diagnosis and appropriate treatment strategies are imperative as the prevalence of PBC increases.…”
Section: Epidemiology Of Diseasementioning
confidence: 99%
“…The condition predominantly affects women older than 40 years, with a female/male ratio of 9:1 . Although the incidence of PBC appears to be stable, the overall prevalence of the disease is increasing . An individual's genetic susceptibility, epigenetic factors, and certain environmental triggers seem to play important roles.…”
Section: Epidemiologymentioning
confidence: 99%